ENHANCING L2 MOTIVATION THROUGH TECHNOLOGY-BASED INSTRUCTION (E.G., APPS GAMES OR ONLINE PLATFORMS) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study explores the role of technology-based instruction in enhancing second language (L2) motivation among learners through the integration of digital tools such as mobile applications, online platforms, and interactive games. In the modern educational context, technology provides a dynamic and engaging environment that supports learner autonomy, instant feedback, and personalized learning experiences. The research emphasizes how platforms like Duolingo, Memrise, and Quizlet, as well as gamified environments, can increase students’ motivation by transforming traditional learning into an interactive process.